The Influence of Brand Image, Customer Experience, and Word of Mouth on The Interest In Rebuying Samsung Smartphone Products at The Alwar Depok Store - Wardhana, Al Fiansyah; Hardini, Resti; Digdowiseiso , Kumba (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
This study aims to determine the influence of brand image, customer experience, and word of mouth on repurchase interest. This study used primary data obtained from the distribution of questionnaires to 96 respondents who had bought Samsung smartphone products at the Alwar Depok store for at least one year of use and processed using Statistical Product and Service Solution (SPSS). The method in this study uses descriptive analysis and inferential analysis. Data were analyzed using instrument tests, multiple linear regression correlations, model feasibility tests, and t-test hypothesis testing. The conclusion of the hypothesis with a partial t-test obtained the results of a calculated value of 2,073 < a table of 1.986 and a significance of 0.041. (0.041<0.05), then on the customer experience variable with a calculated value of 2,363 < table 1,986 and a significance of 0.020. (0.020<0.05) then on the word of mouth variable with a calculated value of 3,360 < 1.986 table and significance of 0.041. (0.041<0.05). So it is partially concluded that the three independent variables have a positive and significant influence on the dependent variable. The results of this study show that the variables of brand image, customer experience, and word of mouth have a positive and significant effect on repurchase interest, this means that if the three independent variables increase, it will increase Samsung's repurchase interest.